Education and Female Entrepreneurship in Asia Public Policies and Private Practices - Maslak, Mary Ann (Palgrave Macmillan US, 2018)
This book examines policies and practices that relate to the education of female entrepreneurs in China, India, Singapore, Indonesia, and Japan. Through both textual and interview data, the book reveals the importance of initiatives that structure entrepreneurships for women, and informal learning through networks in a variety of settings which promotes their understandings of business. Part I offers an overview of the formal and informal sectors of the economy and the international development plans related to each. Part II proffers national development plans and business policies related to female entrepreneurship in each of the five countries. Part III provides stakeholders' perspectives of entrepreneurial learning in each country. Part IV presents conceptual and theoretical models which offer a visual representation of entrepreneurs' learning process. Finally, Part V grapples with the inclusion of informal learning and networking experiences for female entrepreneurs.